2011
DOI: 10.1111/j.1600-0412.2011.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

How do urinary incontinence and urgency affect women's sexual life?

Abstract: Urinary incontinence and urgency have a negative impact on women's sexual life. Thus, a dialogue about sexual function in women with urinary symptoms should become an integral component in clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 25 publications
5
43
0
2
Order By: Relevance
“…Therefore, we used the GRISS to determine the quality of sexual life and the existence and severity of sexual problems affected by USI, UUI, and UMI. Our study results showed that infrequency, dissatisfaction, avoidance, and anorgasmia but not non‐communication, nonsensuality, or vaginismus were significantly higher in the UI group compared with the control group; these results were consistent with those of other studies, suggesting a deterioration of sexual life . In order to determine QoL and distress in our study, when we investigated incontinence subtypes, dissatisfaction was observed at a higher rate in women with UMI and scores of the UDI‐6 and IIQ‐7 were also higher in the UMI group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we used the GRISS to determine the quality of sexual life and the existence and severity of sexual problems affected by USI, UUI, and UMI. Our study results showed that infrequency, dissatisfaction, avoidance, and anorgasmia but not non‐communication, nonsensuality, or vaginismus were significantly higher in the UI group compared with the control group; these results were consistent with those of other studies, suggesting a deterioration of sexual life . In order to determine QoL and distress in our study, when we investigated incontinence subtypes, dissatisfaction was observed at a higher rate in women with UMI and scores of the UDI‐6 and IIQ‐7 were also higher in the UMI group.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have suggested that USI has the greatest impact on sexual life . Detrusor instability or urgency was found to cause greater deterioration in sexual‐health‐related QoL than other subtypes of UI . In parallel with our study results, other authors concluded that mixed UI had a significant impact on sexual function compared with other types of UI …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several studies have suggested that women with OAB have high rates of sexual impairment1112, and lower mean scores for all domains of the FSFI, compared to healthy individuals13. Similarly, urgency and urinary incontinence (UI) have been frequently associated with FSD1415.…”
Section: Discussionmentioning
confidence: 99%
“…Die Prävalenz der koitalen Harninkontinenz wird bei Frauen mit 0,2-66% angegeben (Nilsson et al 2011;Coyne et al 2012;Bekker et al 2009;Jha et al 2012;El-Azab at al. 2011).…”
Section: Weibliche Ejakulationunclassified